Education on The Danger of Consuming Prescriptive Medicine for Health in Nogo Rejo Village, Galang District, Deli Serdang: Edukasi Bahaya Konsumsi Obat Setelan untuk Kesehatan di Desa Nogo Rejo Kec Galang Deli Serdang - Rambe, Robiatun; Pangondian, Aswan; Husein, Saddam; Athaillah, Athaillah; Aini Khairunnisa, Nur (Universitas Haji Sumatera Utara, 2025)
A drug is defined as a collection of several drugs, usually in tablet or capsule form, repackaged in plastic and claimed to cure certain diseases. A drug is readily available in the community, yet there is no guarantee of quality and safety. This community service program aims to educate people about the dangers of using a drug. This activity was conducted using lectures and education methods regarding the health risks of using a drug. The target group was the community, women's groups (PKK), and officials in Nogo Rejo Village, Galang, Deli Serdang. The instruments used included PowerPoint presentations and questionnaires. This community service program began with basic outreach about a drug, and then assessed the community's knowledge of the drug through questionnaires. Pretest and posttest results indicated an increase in knowledge after the activity. The results showed that the community's knowledge in the pretest questionnaire was categorized as poor (0-59%), with an average score of 69%, with a score of sufficient (26%), and a score of good (5%). Meanwhile, the knowledge level in the post-test questionnaire fell into the good knowledge category (75-100%), with an average score of 28%, fair 49%, and sufficient 23%. The conclusion of this community service program is that there was an increase in the knowledge level of the community, PKK cadres, and village officials after being educated about the dangers of using prescription drugs. With this outreach and education, especially in Nogo Rejo Village, the community's knowledge and understanding of using prescription drugs will improve, allowing them to be more cautious and protective when consuming them.